Commercialization of seedlings and açaí pulp (Euterpe oleracea Mart.) in the Municipality of Zé Doca – MA (Research, Society and Development, 2021)
This research aimed to analyze the feasibility of selling seedlings and açaí pulp in the municipality of Zé Doca, state of Maranhão. The work was developed in the municipality of Zé Doca / MA, where the açaí seedlings (Euterpe oleracea Mart.) Are produced and marketed. The data collection used as a basis the use of semi-structured questionnaires, applied directly to four producers in the municipality, where the information obtained by the research was structured by the Microsoft Excel program for the production of graphs and data analysis. The results with the fruit traders point to a significant and growing expansion of açaí in the local market, with expressive values and data analysis that speculate a trend of this economic growth. Its profitability is considerably high regarding the economic return of the family farmer, the circulation of the local açaí has a formal and informal market bias for the generation of income and support of families in the social space, and the growing emergence of consumption and its disparities in economic return the state in the production of açaí. From the analysis it is concluded that both the commercialization of the seedling and the pulp of açaí is profitable to the farmer, considering that the expenses for the production are low and the demand for consumption only tends to increase bringing socioeconomic benefits to these producers, however, it is necessary to provide technical support to traders in order to guide them in the strategies for marketing their products.